2004
DOI: 10.1103/physrevlett.93.107403
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the Radiative and Nonradiative Decay Rates of Single CdSe Nanocrystals through a Controlled Modification of their Spontaneous Emission

Abstract: We present a simple method to measure the radiative and nonradiative recombination rates of individual fluorescent emitters at room temperature. By placing a single molecule successively close and far from a dielectric interface and simultaneously measuring its photoluminescence decay and its orientation, both the radiative and nonradiative recombination rates can be determined. For CdSe nanocrystals, our results demonstrate that the fluorescence quantum efficiency, determined at the single-molecule level, is … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
226
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(239 citation statements)
references
References 22 publications
11
226
1
1
Order By: Relevance
“…For an emission energy of 2.08 eV γ nrad = 0.017±0.006 ns −1 and γ hom rad = 0.065 ± 0.005 ns −1 giving a quantum efficiency of 80 ± 5 %. In figure 10 a) the nonradiative decay rate γ nrad and homogeneous radiative decay rate γ hom rad are shown as a function of the emission energy together with the result found by Brokmann et al [19] for ensembles. The nonradiative decay rate increases with emission energy or equivalently decreases with quantum dot size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For an emission energy of 2.08 eV γ nrad = 0.017±0.006 ns −1 and γ hom rad = 0.065 ± 0.005 ns −1 giving a quantum efficiency of 80 ± 5 %. In figure 10 a) the nonradiative decay rate γ nrad and homogeneous radiative decay rate γ hom rad are shown as a function of the emission energy together with the result found by Brokmann et al [19] for ensembles. The nonradiative decay rate increases with emission energy or equivalently decreases with quantum dot size.…”
Section: Discussionmentioning
confidence: 99%
“…The emission rate will be affected by emission which is reflected at the interface and leads to a controlled modification of the local density of states (LDOS) allowing us to separate radiative and nonradiative decay rate components. This technique has been pioneered by Drexhage for dye molecules [15] and used to determine quantum efficiency of Si nanocrystals [16], erbium ions [17], epitaxially grown InAs quantum dots [18] and colloidal CdSe quantum dots [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…First, the single molecule fluorescence QY is very well defined for CdSe QDs (closely related to CdTe QDs). Indeed, correlated AFM and fluorescence imaging, 199 fluorescence correlation spectroscopy, 200 and dielectric-dependent photoluminescence studies 201 have all demonstrated that the fluorescence QY approaches unity for individual bright QDs. Therefore, although the ensemble CdTe QD QY is ~70%, we can assume that the maximum fluorescence counts in a given time trace correspond to a single CdTe QD QY of ~100%.…”
Section: Single Molecule Fluorescence Quantum Yield Of Qdsmentioning
confidence: 99%
“…The emission efficiency is assessed by the quantum yield (QY) which is given by the ratio between the radiative decay rate and the total decay rate due to radiative and non-radiative relaxations. Excitons in high quality CdSe structures have a QY close to unity 21,22 , while the trion state exhibits a QY ranging from 15 to 50% in this specific sample 11 .…”
Section: Flickeringmentioning
confidence: 99%